Given a function $F:\mathbb{R}^2\to\mathbb{R}$, by the implicit function theorem, the relation $F(x,y) = 0$, defines $y$ implicitly as function of $x$ in a neirbourhood of $(x_0,y_0)$, provided $F(x_0,y_0)=0$ and $\partial F/\partial y (x_0,y_0)\neq 0$.

Moreover, if the implicit function is $\phi$ then for that neirbourhood holds:

$$\frac {d \phi }{d x} = -\frac {\partial F / \partial x} {\partial F / \partial y}.$$

This result can be obtained differentiating the relation $F(x,\phi(x)) = 0$ with respect to x

$$ \frac{dF}{dx}=\frac{\partial F}{\partial x}+\frac{\partial F}{\partial y}\,\frac{\partial \phi}{\partial x}=0 $$ and solving for $d\phi/d x$.

Now, if this could be generalized for the case $F:\mathbb{R}^{n+m}\to\mathbb{R}^m$, then it would be a nice direct way of obtaining the formula for all the partial derivatives of the implicit function (i.e its diferential) by simple implicit diferentiation and matrix algebra.

For example, considering $F(X,Y)=0$, where $X\in \mathbb{R}^n$ and $Y\in \mathbb{R}^m$, suppose suited conditions holds for Y being defined implictly as function of X, say $Y = \Phi(X)$. Taking the total derivative of $F(X,Y)=0$ respect to X we obtain:

$$\frac{dF}{dX} = A + B . D\Phi=0$$ where $A$ and $B$ are the submatrices of $DF$ corresponding to variables $X$ and $Y$ respectively. Then solve for $D\Phi$ by matrix algebra: $$D\Phi=-B^{-1}A$$ I think the process is correct, but I'm not not quite sure if the $dF/dX$ notation for the total derivative is right and don't know how to call $A$ and $B$. (Something like $D_XF$ and $D_YF$?)


1 Answer 1


I personally like to use the notation $\dfrac{\partial F}{\partial X}$ for the $X$-portion of the derivative matrix. However, that notation would be reserved for $A$ and I'd write $B=\dfrac{\partial F}{\partial Y}$. You should be writing $g(X) = F(X,\Phi(X))$ and then writing $$Dg = A+B\cdot D\Phi = \frac{\partial F}{\partial X}+\frac{\partial F}{\partial Y}D\Phi\,.$$ As you commented, this gives the usual formula for implicit differentiation that follows from the Implicit Function Theorem, assuming $B=\dfrac{\partial F}{\partial Y}$ is nonsingular.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.